Development of educational programmes for the health professions. - World Health Organization (Geneva : WHO, 1973)
Hoe staat het met de bijscholing van mensen uit de medische sector?
Includes bibliographical references.
Keywords: Medical teaching personnel; Medicine -- Study and teaching